2016
DOI: 10.1063/1.4942605
|View full text |Cite
|
Sign up to set email alerts
|

On the manifestation of phosphorus-vacancy complexes in epitaxial Si:P films

Abstract: In situ doped epitaxial Si:P films with P concentrations >1 × 1021 at./cm3 are suitable for source-drain stressors of n-FinFETs. These films combine the advantages of high conductivity derived from the high P doping with the creation of tensile strain in the Si channel. It has been suggested that the tensile strain developed in the Si:P films is due to the presence of local Si3P4 clusters, which however do not contribute to the electrical conductivity. During laser annealing, the Si3P4 clusters are expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…7) are indeed negative (−0.16 eV and −0.6 eV). 27 Therefore, our finding suggests that from an energetic perspective, P n V clusters could be present both as monovacancies (P 4 V) and divacancies (P 6 V 2 ) in the Si:P lattice. Hence, P atoms are expected to form local nearest neighbor arrangements in the presence of vacancies.…”
Section: Understanding the Structure Of Si:p Filmsmentioning
confidence: 93%
See 1 more Smart Citation
“…7) are indeed negative (−0.16 eV and −0.6 eV). 27 Therefore, our finding suggests that from an energetic perspective, P n V clusters could be present both as monovacancies (P 4 V) and divacancies (P 6 V 2 ) in the Si:P lattice. Hence, P atoms are expected to form local nearest neighbor arrangements in the presence of vacancies.…”
Section: Understanding the Structure Of Si:p Filmsmentioning
confidence: 93%
“…The data points of the as-grown samples fall all on the same line. As we reported elsewhere, 27 using a high resolution CDOBS measurement technique enabled us to identify the chemical surroundings of the vacancies as well. It was deduced that vacancies were decorated with P atoms similar to P 4 V complexes, which were predicted in the Influence of vacancy on P arrangement section of this paper.…”
Section: Experimental Verification Of P 4 V Complexes Using Pasmentioning
confidence: 99%
“…At the same time, it will be shown that larger C-related clusters give rise to a deeper band of hole traps closer to the epitaxial interface. This can partly explain the observed loss in strain of the stressor layer after annealing [6], [13]. …”
Section: Resultsmentioning
confidence: 81%
“…The generation of free carriers requires achieving high concentration of electrically active dopants, typically controlled by doping and annealing techniques. The selective growth of in-situ doped epitaxial Si:P [1][2][3][4] is a major innovation that can significantly reduce source-drain external resistance and simultaneously act as stressor for advanced field effect transistor options beyond 3nm including gate-all-around (GAA) nanowire and FinFET devices. [5][6][7] The continuing device scaling demands for ever-increasing phosphorus concentration [P] in epitaxial Si:P. There has been significant efforts to increase phosphorus concentration [P] in epitaxial Si:P, and the highest [P] achieved nowadays is about 3x10 21 at./cm 3 by state-of-the-art epitaxial Si:P processes, virtually limited by its solid solubility.…”
mentioning
confidence: 99%